Effects of positive mood on attentional breadth for emotional stimuli - Grol, Maud; Raedt, Rudi De (Frontiers in Psychology, 2014)
Although earlier studies have related positive emotions to attentional broadening, recent findings point out the complexity of this relation and show that these broadening effects interact with factors such as characteristics of the information that is presented. Besides stimuli characteristics, individual characteristics such as the presence of depressive symptoms could also influence the broadening effects as depressive symptoms have previously been related to a more narrow attentional scope. Therefore, the aim of this study was to further investigate the attentional broadening effects of positive emotions, testing whether this is influenced by the emotional valence of the information presented and secondly, how the presence of depressive symptoms might interact with this relationship. We used a performance-based measure to assess fluctuations in attentional broadening for positive, neutral, and negative stimuli. We assessed the presence and severity of depressive symptoms in an unselected study sample and tested whether these symptoms moderate the relationship between induced positive mood and attentional breadth for emotional information. Results showed no direct relation between positive mood and attentional breadth, regardless of the emotional valence of the stimuli. However, the presence of depressive symptoms moderated this relationship in such a way that among low levels of depressive symptoms, positive mood was related to attentional broadening specifically when positive information was presented, while at high levels of depressive symptoms this relation was reversed. The current findings suggest that both stimuli characteristics, individual characteristics and their interplay should be taken into account when investigating the broadening effects of positive emotions.